Complete Obstruction of Endotracheal Tube in an Infant with a Retropharyngeal and Anterior Mediastinal Abscess - Dennis B. Thapa; Nathaniel H. Greene; Andrea G. Udani (Hindawi Limited, 2017)
Intraoperative ventilatory failure is not an uncommon complication; however, acute endotracheal obstruction by a foreign body or blood clot can be difficult to quickly discriminate from other causes. Once the diagnosis is made, quick action is needed to restore ventilation. The ultimate solution is to exchange the endotracheal tube; however, there can be other ways of resolving this in situations where reintubation would be difficult or unsafe. This case report discusses such an event in an infant with multiple airway challenges including a retropharyngeal and anterior mediastinal abscess. We have also formulated a pathway based on various case reports involving complete ETT obstruction.